Intermedial Ontologies: Strategies of Preparedness, Research and Design in Real Time Performance Capture - Delbridge, Matthew; Roihankorpi, Riku (Nordic Theatre Studies, 2014)
The paper introduces and inspects core elements relative to the ‘live’ in performances that utilise real time Motion Capture (MoCap) systems and cognate/reactive virtual environments by drawing on interdisciplinary research conducted by Matthew Delbridge (University of Tasmania), and the collaborative live MoCap workshops carried out in projects DREX and VIMMA (2009-12 and 2013-14, University of Tampere). It also discusses strategies to revise manners of direction and performing, practical work processes, questions of production design and educational aspects peculiar to technological staging. Through the analysis of a series of performative experiments involving 3D real time virtual reality systems, projection mapping and reactive surfaces, new ways of interacting in/with performance have been identified. This poses a unique challenge to traditional approaches of learning about staging, dramaturgy, acting, dance and performance design in the academy, all of which are altered in a fundamental manner when real time virtual reality is introduced as a core element of the performative experience. Meanwhile, various analyses, descriptions and theorisations of technological performance have framed up-to-date policies on how to approach these questions more systematically. These have given rise to more sophisticated notions of preparedness of performing arts professionals, students and researchers to confront the potentials of new technologies and the forms of creativity and art they enable. The deployment of real time Motion Capture systems and co-present virtual environments in an educational setting comprise a peculiar but informative case of study for the above to be explored.